Implications of climate change on water availability in a seasonally dry tropical forest in the Northeast of Brazil - de Sousa Nascimento, Robson; Peixoto Borges, Valéria; de Carvalho Diniz Melo, Davi (Revista Ceres, 2025)
Climate change is already affecting life on Earth and mitigation measures must be taken, which require proper identification of the regions most vulnerable to these changes. This study assesses the impact of climate change on water availability (water surplus, water deficit and precipitation minus evapotranspiration) and climate classification across the Caatinga biome, located within the Brazilian semiarid region. To obtain the water surplus and water deficit, the water balance of Thornthwaite & Matther (1955) was applied considering the current scenario (historical series from 1961 to 2015); the optimistic scenario, considering the Representative Concentration Pathway (RCP) for a radiative forcing of 4.5 W.m-2 (RCP4.5), i.e., considering a temperature increase of 1.5 ºC and a reduction in rainfall from 15%; and pessimistic, considering a radiative forcing of 8.5 W.m-2 (RCP8.5), i.e. taking an increase in temperature of 4.0 ºC and a reduction in rainfall from 20%. The results showed that the Caatinga was strongly impacted, especially in the pessimistic scenario, with no water surplus and a negative water balance. For the optimistic scenario, only a small portion presented a water-surplus and a positive water balance. Projections also showed that a large part of the Caatinga changed from semiarid to arid climate.